Manufacturing method for RTB sintered magnets
By controlling oxygen content and using a specific alloy composition, the method improves pulverization efficiency and magnetic properties of R-T-B sintered magnets, addressing the challenges of high performance and cost-effectiveness.
Patent Information
- Application Number
- JP2020056173
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-03-26
AI Technical Summary
Existing methods for manufacturing R-T-B sintered magnets face challenges in achieving high coercive force (HcJ) and residual magnetic flux density (Br) while minimizing the use of expensive heavy rare earth elements and maintaining low oxygen content, as they often result in deteriorated pulverization efficiency and magnetic properties.
A method involving the use of a specific composition of R-T-B alloy powders, including additive and main alloy powders, pulverized in a humidified inert gas atmosphere to control oxygen content between 1000 ppm and 3000 ppm, resulting in an R-T-B sintered magnet with improved magnetic properties and reduced heavy rare earth element content.
The method effectively suppresses pulverization efficiency deterioration and enhances both Br and HcJ by controlling oxygen content and particle size, leading to high-performance R-T-B sintered magnets suitable for various applications.
Smart Images

Figure 0007600531000008 
Figure 0007600531000001 
Figure 0007600531000002
Abstract
Description
[Technical field]
[0001] The present application relates to a method for producing an RTB based sintered magnet. [Background technology]
[0002] RTB sintered magnets (R is at least one rare earth element and always includes Nd, and T is at least one transition metal element and always includes Fe) are known as the highest performance magnets among permanent magnets, and are used in a wide variety of applications such as voice coil motors (VCM) for hard disk drives, motors for electric vehicles (EV, HV, PHV), motors for industrial equipment, and other motors and home appliances.
[0003] RTB sintered magnets are mainly R2T 14 It is composed of a main phase made of B compounds and a grain boundary phase (two-particle grain boundary or multiple-point grain boundary) located at the grain boundary part of this main phase. 14 B compounds are ferromagnetic materials with high saturation magnetization and anisotropic magnetic field, and form the basis of the properties of RTB sintered magnets.
[0004] An RTB sintered magnet is manufactured, for example, through a process of preparing an alloy powder, a process of press-molding the alloy powder to produce a powder compact, and a process of sintering the powder compact. The alloy powder is manufactured, for example, by the following method. First, an alloy is manufactured from molten metals of various raw metals by an ingot method, a strip casting method, or the like. The obtained alloy is subjected to a pulverization process to obtain an alloy powder having a predetermined particle size distribution. This pulverization process usually includes a coarse pulverization process and a fine pulverization process, the former of which utilizes, for example, the hydrogen embrittlement phenomenon, and the latter of which uses, for example, an airflow pulverizer (jet mill).
[0005] Such RTB sintered magnets have a coercive force H cJ (Hereafter, simply "H cJ ") decreases, and irreversible thermal demagnetization occurs. Therefore, especially when used in electric vehicle motors, high HcJ To maintain the H cJ is required.
[0006] Conventionally, H cJ To improve the residual magnetic flux density B r (Hereinafter, simply "B r For this reason, in recent years, heavy rare earth elements have been diffused from the surface to the inside of RTB sintered magnets to concentrate the heavy rare earth elements in the outer periphery of the main phase crystal grains, thereby improving the B r While suppressing the decline of cJ A method has been adopted to obtain
[0007] However, heavy rare earth elements such as Dy are expensive and have problems such as price fluctuations. Therefore, the amount of heavy rare earth elements such as Dy used is minimized to improve the H content of RTB sintered magnets. cJ There is a demand for technologies that can improve this.
[0008] Patent Document 1 describes a method for producing an R2T alloy by lowering the B content compared to conventional RTB alloys and adding one or more metal elements M selected from Al, Ga, and Cu. 17 The R2T 17 Transition metal-rich phase (R6T 13 It is described that by ensuring a sufficient volume ratio of Dy), it is possible to obtain an RTB rare earth sintered magnet with high coercivity while suppressing the Dy content.
[0009] In addition, H other than the method described in Patent Document 1 cJ Techniques for improving performance, such as improving the powder density, include, for example, making the structure finer and reducing the amount of oxygen contained. In addition to improving performance, RTB sintered magnets are also required to be less expensive. Techniques for reducing cost, such as improving the crushing efficiency, are also required.
[0010] Patent Document 2 discloses a method for improving the efficiency of pulverization by performing jet mill pulverization using a humidified inert gas stream with a dew point of −20° C. to 0° C. A similar method is also described in Patent Document 3. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] International Publication No. 2013 / 008756 [Patent Document 2] Japanese Patent Application Publication No. 8-148317 [Patent Document 3] Japanese Patent Application Publication No. 6-140220 Summary of the Invention [Problem to be solved by the invention]
[0012] When producing an RTB sintered magnet with a reduced oxygen content, for example an oxygen content of 3000 ppm or less, high-purity nitrogen gas, for example, is used as the inert gas to prevent oxidation of the powder particles during the grinding process.
[0013] According to the study by the present inventors, it was found that when jet mill pulverization is performed using an inert gas such as high-purity nitrogen gas, the expected high performance cannot be achieved by reducing oxygen. In addition, when trying to improve performance by making the powder finer, the pulverization efficiency is sacrificed. Regarding the pulverization efficiency, there are methods disclosed in Patent Documents 2 and 3, but the configurations disclosed in Patent Documents 2 and 3 are technologies that increase the oxygen content to over 3000 ppm in order to suppress reactivity, and cannot be applied to improve performance by reducing oxygen. The embodiment of the present disclosure reduces the content of heavy rare earth elements to achieve high B while suppressing the deterioration of pulverization efficiency during jet mill pulverization even if the pulverized particle size of the fine powder is reduced. r and high H cJ The present invention provides a method for producing an RTB magnet that achieves the above object. [Means for solving the problem]
[0014] A non-limiting exemplary embodiment of a method for producing an RTB based sintered magnet according to the present disclosure is a method for producing an RTB based sintered magnet (R is at least one rare earth element and always includes Nd, and T is Fe or Fe and Co), comprising the steps of: preparing an additive alloy powder containing 33 to 69 mass% of R1: (R1 is at least one rare earth element and 50 mass% or more of R1 is Pr), 0.2 to 0.8 mass% of B, 0.8 to 3.0 mass% of Cu, 1.8 to 10 mass% of Ga, and 15 to 60 mass% of T; and preparing a main alloy powder containing 28.5 to 33.0 mass% of R, 0.80 to 1.0 mass% of B, 0.1 to 0.4 mass% of Ga, and 64 to 70 mass% of T. preparing a mixed alloy powder containing 1 to 16 mass% of the additive alloy powder and 84 to 99 mass% of the main alloy powder; supplying the mixed alloy powder to a jet mill device having a crushing chamber filled with an inert gas to crush the mixed alloy powder to obtain a fine powder having an average particle size of 2.0 μm to 4.5 μm; and producing a sintered body of the fine powder, wherein the Pr content of the additive alloy powder is greater than the Pr content of the main alloy powder, the inert gas is humidified, and the RTB based sintered magnet has an oxygen content of 1000 ppm to 3000 ppm, R: 28.5 mass% to 33.0 mass%, B: 2.0 mass% to 2.5 mass%, and C: 2.0 mass% to 2.5 mass%. : 0.85 mass% or more and 0.91 mass% or less, Cu: 0.05 mass% or more and 0.50 mass% or less, Ga: 0.3 mass% or more and 0.7 mass% or less, and T: 63 mass% or more and 70 mass% or less (T is Fe or Fe and Co), where the T content (mass%) is [T] and the B content (mass%) is [B], the relationship [T] / 55.85>14×[B] / 10.8 is satisfied.
[0015] In one embodiment, the RTB based sintered magnet has an R content of 31 mass % or less.
[0016] In one embodiment, the inert gas is nitrogen gas.
[0017] In one embodiment, the step of producing a sintered body of the fine powder includes a step of producing a powder compact from the fine powder by wet pressing in a magnetic field or by pressing in a magnetic field in an inert gas atmosphere, and a step of sintering the powder compact.
[0018] In one embodiment, the average particle size of the fine powder in the step of obtaining the fine powder is 2.0 μm or more and 3.5 μm or less. Effect of the Invention
[0019] According to the embodiment of the present disclosure, even if the pulverized particle size of the fine powder is reduced, the deterioration of the pulverization efficiency during jet mill pulverization is suppressed, and the content of heavy rare earth elements is reduced to obtain a high B r and high H cJ It is possible to provide a method for producing an RTB magnet that achieves the above. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a diagram showing a schematic configuration example of an RTB sintered magnet alloy crushing system 1000 according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] As a result of the study, the inventors of the present invention found that in the case of producing an RTB-based sintered magnet with a reduced oxygen content, when the powder particles are reduced in size in the grinding process, in addition to the deterioration of grinding efficiency, the powder particles are nitrided by an inert gas (particularly when dry nitrogen gas is used as the inert gas) in the grinding process, and the desired improvement in magnetic properties due to the reduction in the size of the ground particles cannot be obtained. As a result of further study, the inventors of the present invention found that the deterioration of powder particles due to the inert gas can be reduced by using a humidified inert gas. This is believed to be because the formation of an oxide film on the surface of the powder particles makes it possible to prevent the introduction of an inert gas (particularly nitrogen gas) into the powder particles, thereby suppressing the deterioration (nitridation) of the powder particles due to the inert gas. It has been known in the past that the grinding efficiency is deteriorated when the powder particles are reduced in size in the grinding process, and that this deterioration can be improved by using a humidified inert gas flow (for example, Patent Document 2 and Patent Document 3). However, when pulverizing using a humidified inert gas stream, it was thought that the powder particles would be oxidized and the magnetic properties would deteriorate, so when manufacturing RTB sintered magnets with a reduced oxygen content to improve their magnetic properties, pulverization using a humidified inert gas stream was not actively carried out in an attempt to make the pulverized particles smaller (for example, the oxygen content of the fine powder in Patent Document 2 is relatively high at 4500 ppm and 4900 ppm, and Patent Document 3 does not disclose the oxygen content). However, the present inventors conducted extensive research based on the above-mentioned knowledge that the deterioration of powder particles due to inert gas can be reduced by using a humidified inert gas, and as a result, they unexpectedly found that, in the RTB sintered magnets finally obtained, when the powder particles are humidified and milled so that the oxygen content falls within a specific range, it is possible to suppress both the deterioration (nitridation) of the powder particles and the deterioration of the magnetic properties due to oxidation caused by humidification. Generally, the process after pulverization in which the oxygen content of an RTB based sintered magnet increases is the process of forming a sintered body by molding and sintering fine powder, but the increase in the oxygen content of an RTB based sintered magnet is small (for example, between 50 ppm and 300 ppm). Therefore, the oxygen content of an RTB based sintered magnet can be adjusted by the pulverization process.Furthermore, as a result of investigations, the inventors of the present invention have found that when humid pulverization according to the present disclosure is performed on a mixed alloy powder obtained by mixing a master alloy powder and an additive alloy powder having a specific composition, H is improved as compared with the case of pulverization without humidification. cJ That is, the present disclosure specifies the composition of the R-T-B sintered magnet within a specific range using an additive alloy powder and a master alloy powder having a specific composition. Further, in the pulverization step of the R-T-B sintered magnet, humid pulverization is performed so that the oxygen content of the obtained R-T-B sintered magnet falls within a specific range (1000 ppm or more and 3000 ppm or less, preferably 1000 ppm or more and 2500 ppm or less) to reduce the particle size of the powder particles (the average particle size is 2.0 μm or more and 4.5 μm or less, preferably the average particle size is 2.0 μm or more and 3.5 μm or less). By doing so, it is possible to reduce the deterioration of magnetic properties due to oxidation and nitridation in the pulverization step, suppress the deterioration of pulverization efficiency during jet mill pulverization, reduce the content of heavy rare earth elements, and obtain high B r and high H cJ It has been found that an R-T-B sintered magnet can be obtained.
[0022] <Method for manufacturing R-T-B sintered magnet> The method for manufacturing an R-T-B sintered magnet according to the present disclosure comprises (1) a step of preparing an additive alloy powder; (2) a step of preparing a master alloy powder; (3) a step of preparing a mixed alloy powder; (4) a step of supplying the mixed alloy powder to a jet mill apparatus filled with an inert gas in a pulverization chamber to pulverize the mixed alloy powder and obtaining fine powder having an average particle size of 2.0 μm or more and 4.5 μm or less; (5) a step of producing a sintered body of the fine powder; and the inert gas is humidified. The average particle size (d50) can be measured by an air flow dispersion type laser diffraction method.
[0023] <R-T-B sintered magnet> The RTB sintered magnet of the present disclosure has an oxygen content of 1000 ppm or more and 3000 ppm or less by mass. By setting the oxygen content to 1000 ppm or more and 3000 ppm or less, it is possible to suppress the deterioration of magnetic properties caused by nitriding of powder particles by the inert gas due to insufficient humidification of the inert gas in the step (4) of obtaining fine powder, or the deterioration of magnetic properties caused by oxidation of powder particles due to humidification. To obtain higher magnetic properties, the oxygen content of the RTB sintered magnet is preferably 1000 ppm or more and 2500 ppm or less, and more preferably 1000 ppm or more and 2000 ppm or less.
[0024] Furthermore, the RTB based sintered magnet according to the present invention (sometimes simply referred to as "sintered magnet") has the following properties: R:28.5~33.0% by mass, B: 0.85~0.91% by mass, Cu:0.05~0.50% by mass, Ga: 0.3 to 0.7 mass%; and T: 63 to 70% by mass, When the T content (mass %) is [T] and the B content (mass %) is [B], the RTB sintered magnet satisfies [T] / 55.85>14×[B] / 10.8.
[0025] The above composition allows the magnet to contain less B than typical RTB sintered magnets, while also containing Ga, etc. This allows the formation of RT-Ga phases, especially at multi-point grain boundaries, and R-Cu-Ga phases, especially at two-particle grain boundaries, respectively, and reduces the heavy rare earth element content to achieve high B. r and high H cJ Here, the RT-Ga phase is typically Nd6Fe 13 This phase is made up of Ga compounds. R6T 13 The Ga compound is La6Co 11 It has a Ga3 type crystal structure. 13 Depending on the state, Ga compounds may exhibit the following properties: R6T 13-δ Ga 1+δFor example, when a relatively large amount of Cu and Al is contained in an RTB sintered magnet, R6T 13-δ (Ga 1-x-y Cu x Al y ) 1+δ The R-Cu-Ga phase is a phase in which a portion of Ga in the R-Ga phase is replaced with Cu, and contains R: 70% by mass to 95% by mass, Ga: 5% by mass to 30% by mass, and T(Fe): 20% by mass or less (including 0), and examples of such phases include R3(Ga,Cu)1 compounds.
[0026] Each component contained in the RTB sintered magnet will now be described in detail.
[0027] (R:28.5~33.0% by mass) R is at least one rare earth element and always includes Nd. The R content (R amount) is 28.5 to 33.0 mass%. If R is less than 28.5 mass%, densification during sintering may be difficult, and if it exceeds 33.0 mass%, the main phase ratio decreases and high B r There is a risk that you will not be able to obtain the necessary information. The amount of R is preferably 31% by mass or less, and more preferably 29 to 31% by mass. r can be obtained.
[0028] (B:0.85~0.91% by mass) The B content (B amount) of the sintered magnet is 0.85 to 0.91 mass%. If the B amount is less than 0.85 mass%, the R2T 17 Phase is generated and high H cJ If the content exceeds 0.91 mass%, the amount of RT-Ga phase produced is too small, and high H cJ There is a risk that it will not be possible to obtain
[0029] (Cu:0.05~0.50% by mass) The Cu content (Cu amount) of the sintered magnet is 0.05 to 0.50 mass%. If the Cu amount is less than 0.05 mass%, high H cJ If it exceeds 0.50 mass%, the sintering property may deteriorate and a high H cJ There is a risk that it will not be possible to obtain
[0030] (Ga:0.3~0.7% by mass) The Ga content (Ga amount) of the sintered magnet is 0.3 to 0.7% by mass. If the Ga amount is less than 0.3% by mass, the amount of RT-Ga phase produced is too small, and the R2T 17 The phase cannot be eliminated, and high H cJ If it exceeds 0.7 mass%, unnecessary Ga will be present, and the main phase ratio will decrease, resulting in a decrease in B. r There is a risk of a decline.
[0031] (T:63~70% by mass) T is Fe or Fe and Co. The content of T (T amount) is 63.0% by mass to 70% by mass. If the content of T is less than 63.0% by mass or exceeds 70% by mass, the B r There is a risk that it will decline.
[0032] The content of B satisfies the following formula (1). [T] / 55.85>14×[B] / 10.8 By satisfying formula (1), the B content is less than that of a typical RTB sintered magnet. A typical RTB sintered magnet contains R2T, which is the main phase. 14 In addition to the B phase, there is a soft magnetic phase, R2T 17 To prevent the formation of any phase, the composition is set such that [T] / 55.85 (atomic weight of Fe) is less than 14 × [B] / 10.8 (atomic weight of B) ([T] is the Fe content in mass %). Unlike typical RTB based sintered magnets, the RTB based sintered magnet of the present invention is specified by formula (1) such that [T] / 55.85 is greater than 14 × [B] / 10.8. Note that since the main component of T in the RTB based sintered magnet of the present invention is Fe, the atomic weight of Fe is used.
[0033] (Inevitable impurities and other elements) Furthermore, the RTB sintered magnet of the present invention can contain Cr, Mn, Si, La, Ce, Sm, Ca, Mg, etc., as unavoidable impurities that are usually contained in didymium alloys (Nd-Pr), electrolytic iron, ferroboron, etc. Such elements may be contained in a total amount of, for example, about 2.0 mass% or less. At this level, it is possible to obtain a high B r and high H cJ It is quite possible to obtain an RTB based sintered magnet having the above properties. Furthermore, examples of unavoidable impurities that may be mixed in during the manufacturing process include O (oxygen), N (nitrogen), and C (carbon). Furthermore, the RTB based sintered magnet of the present disclosure may further contain one or more other elements (elements that are intentionally added other than the unavoidable impurities). For example, such elements may contain small amounts (each about 0.2 mass% or less) of Ag, Zn, In, Sn, Ti, Ge, Y, H, F, P, S, V, Ni, Mo, Hf, Ta, W, Nb, Zr, etc.
[0034] The oxygen content of RTB sintered magnets is in the range of 1000 ppm to 3000 ppm (preferably 1000 ppm to 2500 ppm). Both nitridation of powder particles and oxidation due to humidification can be suppressed to obtain high magnetic properties. As described later, the amount of oxygen contained in RTB sintered magnets can be adjusted by the milling process. The RTB based sintered magnet of the present invention may contain R, B, Cu, and Ga in the above-mentioned ranges, with the balance being Fe and unavoidable impurities. In other words, it is possible to obtain an RTB based sintered magnet that contains only B, R, Cu, Ga, Fe, and unavoidable impurities, and does not contain any other intentionally added elements.
[0035] (1) A process for preparing additive alloy powder In this step, additive alloy powder is prepared for use in producing the sintered magnet. The additive alloy powder having a predetermined composition described later can be manufactured by the same method as the known manufacturing method of RTB sintered magnets. For example, flake-shaped alloy flakes are produced by an ingot method using a mold casting or a strip casting method in which a molten alloy is quenched using a cooling roll. The obtained flake-shaped alloy flakes are subjected to hydrogen pulverization to obtain a coarsely pulverized powder (additive alloy powder) having a size of, for example, 1.0 mm or less.
[0036] The composition of the additive alloy powder is: R1: 33~69% by mass, B:0.2~0.8% by mass, Cu:0.8~3.0% by mass, Ga: 1.8~10% by mass, T: 15 to 60 mass%, including.
[0037] The reasons for limiting the amount of each element contained in the additive alloy powder will be described below.
[0038] (R1:33~69% by mass) R1 is at least one rare earth element, and 50 mass % or more of the total of R1 is Pr.
[0039] By making Pr 50 mass % or more of the total R1, grain boundaries containing Pr are more likely to be formed in the grain boundaries of the resulting RTB based sintered magnet, making it possible to obtain excellent magnetic properties.
[0040] The content of R1 in the additive alloy powder (R1 amount) is 33 to 69 mass%. If the R1 amount is less than 33 mass%, R2T 14 Since the amount of R1 is too small relative to the stoichiometric composition of B, it may be difficult to generate the R-Ga phase and the R-Ga-Cu phase. If the amount of R1 exceeds 69 mass%, the amount of R1 is too large, which may cause problems with oxidation of R1, leading to deterioration of magnetic properties and a risk of fire, which may cause problems in production.
[0041] The amount of R1 is preferably 40 to 60 mass %. The Pr content of the additive alloy powder is set to be higher than the Pr content of the main alloy powder.
[0042] (B:0.2~0.8% by mass) The B content (B amount) of the additive alloy powder is 0.2 to 0.8 mass%. B reacts with R and T to form the main phase R2T 14 It is an element necessary for producing B type compounds. If the B content is less than 0.2 mass%, R2T 14 The amount of B-type compounds produced is small, and R2T is contained in the added alloy powder. 17 Therefore, the H phase of the final sintered magnet is cJ If the B content exceeds 0.8 mass%, the B content in the main alloy powder must be reduced, and the R2T 17 The H phase is generated in the final sintered magnet. cJ There is a risk of a decline. The amount of B is preferably 0.2 to 0.7 mass %.
[0043] (Cu:0.8~3.0% by mass) The Cu content (Cu amount) of the additive alloy powder is 0.8 to 3.0 mass%. If the Cu amount is less than 0.8 mass%, the Cu amount in the finally obtained sintered magnet will be insufficient, and H cJ If the Cu content exceeds 3.0 mass %, the sinterability of the mixed alloy powder containing the additive alloy powder and the main alloy powder may deteriorate, and the H of the sintered magnet may decrease. cJ There is a risk of a decline. The Cu content is preferably 1.5 to 2.6 mass %.
[0044] (Ga:1.8~10% by mass) The Ga content of the additive alloy powder is 1.8 to 10 mass%. If the Ga content is less than 1.8 mass%, the Ga content in the main alloy powder must be increased, and an RT-Ga phase is generated in the main alloy powder, resulting in a decrease in the H content of the finally obtained sintered magnet. cJ If the content exceeds 10 mass%, the RT-Ga phase is generated in the added alloy powder, and the H content of the finally obtained sintered magnet may decrease. cJ There is a risk of a decline. The Ga content is preferably 3 to 8 mass %.
[0045] (T:15~60% by mass) T is Fe or Fe and Co. The content of T in the additive alloy powder is 15 to 60 mass%. It reacts with R and T to form the main phase R2T 14 It is an element necessary for producing B type compounds. When the amount of T is less than 15 mass%, R2T 14 The amount of B-type compounds produced is small, so the H cJ When the T content exceeds 60 mass%, the T content in the main alloy powder must be reduced, and the R2T content in the main alloy powder is reduced. 17 The H phase is generated in the final sintered magnet. cJ There is a risk of a decline. The amount of T is preferably 20 to 50% by mass.
[0046] (Inevitable impurities and other elements) The additive alloy powder may contain Cr, Mn, Si, La, Ce, Sm, Ca, Mg, etc. as inevitable impurities. The elements listed above as inevitable impurities may also be intentionally added. Such elements may be contained in total, for example, at about 1.0 mass% or less. At this level, high H cJ It is quite possible to obtain an RTB based sintered magnet having the above properties. Furthermore, examples of unavoidable impurities that may be mixed in during the manufacturing process include O (oxygen), N (nitrogen) and C (carbon). The RTB based sintered magnet of the present invention may also contain one or more other elements (elements that are intentionally added other than the unavoidable impurities). For example, such elements may include small amounts (each about 0.1 mass % or less) of Ag, Zn, In, Sn, Ti, Ge, Y, H, F, P, S, V, Ni, Mo, Hf, Ta, W, Nb, Zr, etc.
[0047] In addition, multiple types of additive alloy powders may be prepared as long as they are within the composition range of the additive alloy powder described above. In this case, the total amount of the multiple types of additive alloy powders should be 1 to 16 mass% when the mixed alloy powder is 100 mass%.
[0048] (2) Preparing the main alloy powder In this step, the main alloy powder used to manufacture the sintered magnet is prepared. The main alloy powder can be produced by the same method as the additive alloy powder. For example, flake-shaped alloy flakes are produced by an ingot method using a mold casting or a strip casting method in which a molten alloy is quenched using a cooling roll. The obtained flake-shaped alloy flakes are then hydrogen-pulverized to obtain a coarsely pulverized powder (main alloy powder) having a size of, for example, 1.0 mm or less.
[0049] The composition of the main alloy powder is adjusted so that the contents of R, B, Ga, and T fall within the following ranges. R:28.5~33.0% by mass, B: 0.80~1.00% by mass, Ga: 0.1 to 0.4 mass%; and T:64~70% by mass
[0050] The reasons for limiting the content of each element in the main alloy powder will be described below.
[0051] (R:28.5~33.0% by mass) R is at least one rare earth element and always includes Nd. The R content (R amount) of the main alloy powder is 28.5 to 33.0 mass%. If the R amount is less than 28.5 mass%, H cJ If the R content exceeds 33.0 mass%, B r There is a risk of a decline.
[0052] (B:0.80~1.00% by mass) The B content (B amount) of the main alloy powder is 0.80 to 1.10 mass%. B reacts with R and T to form the main phase R2T 14 It is an element necessary for producing B type compounds. If the B content is less than 0.80 mass%, R2T 14 The amount of B-type compounds produced is small, and R2T is contained in the added alloy powder. 17 Therefore, the H phase of the final sintered magnet is easily generated. cJIf the B content exceeds 1.10 mass%, the B content in the added alloy powder must be reduced, and the R2T 17 The H phase is generated in the final sintered magnet. cJ There is a risk of a decline.
[0053] (Ga:0.1~0.4% by mass) The Ga content (Ga amount) of the main alloy powder is 0.1 to 0.4 mass%. If the Ga amount is less than 0.1 mass%, the amount of the R-Ga phase and the R-Ga-Cu phase formed is too small, and H cJ If the Ga content exceeds 0.4 mass %, an RT-Ga phase is generated in the main alloy powder, and the H of the finally obtained sintered magnet may decrease. cJ There is a risk of a decline.
[0054] (T:64~70% by mass) T is Fe or Fe and Co. The T content (T amount) of the main alloy powder is 64 to 70 mass%. If the T amount is less than 64 mass%, H cJ If the T content exceeds 70 mass%, R2T 17 The phase is generated and H cJ There is a risk of a decline. When the total amount of T is taken as 100 mass%, for example, 0 to 10 mass% of T may be replaced with Co. In other words, of the total amount of T, 90 to 100 mass% is Fe and 0 to 10 mass% is Co.
[0055] (Inevitable impurities and other elements) The main alloy powder may contain Cr, Mn, Si, La, Ce, Sm, Ca, Mg, etc. as inevitable impurities. The elements listed above as inevitable impurities may also be intentionally added. Such elements may be contained in a total amount of, for example, about 2.0 mass% or less. At this level, high H cJIt is quite possible to obtain an RTB based sintered magnet having the above properties. Furthermore, examples of unavoidable impurities that may be mixed in during the manufacturing process include O (oxygen), N (nitrogen) and C (carbon). The RTB based sintered magnet of the present invention may also contain one or more other elements (elements that are intentionally added other than the unavoidable impurities). For example, such elements may include small amounts (each about 0.2 mass% or less) of Ag, Zn, In, Sn, Ti, Ge, Y, H, F, P, S, V, Ni, Mo, Hf, Ta, W, Nb, Zr, etc.
[0056] In addition, multiple types of main alloy powders may be prepared as long as they are within the composition range of the main alloy powder described above. In this case, the total amount of the multiple types of main alloy powders should be 84 to 99 mass% when the mixed alloy powder is 100 mass%.
[0057] (3) preparing mixed alloy powder The additive alloy powder and the main alloy powder are mixed to prepare a mixed alloy powder, where 1 to 16 mass % of the additive alloy powder and 84 to 99 mass % of the main alloy powder are mixed, assuming that the mixed alloy powder is 100 mass %. If the amount of the added alloy powder is less than 1 mass%, the amount of the added alloy powder is too small to suppress the formation of the RT-Ga phase, and the H cJ If the amount of the added alloy powder exceeds 16 mass%, B r The mixed alloy powder is prepared by mixing the additive alloy powder and the main alloy powder in a known device such as a V-type mixer, and then feeding the mixed alloy powder to a jet mill device for pulverization to obtain a fine powder having an average particle size of 2.0 μm to 4.5 μm.
[0058] (4) A process in which the mixed alloy powder is fed into a jet mill device whose grinding chamber is filled with an inert gas to grind the mixed alloy powder, thereby obtaining a fine powder having an average particle size of 2.0 μm or more and 4.5 μm or less. <Crushing system> First, a grinding system that can be used in the manufacturing method of the RTB sintered magnet according to the present disclosure will be illustrated with reference to Fig. 1. Fig. 1 is a schematic diagram showing a configuration example of a grinding system 1000 in this embodiment. In this example, the RTB sintered magnet alloy grinding system 1000 includes a jet mill device 100, a cyclone collection device 200, and a bag filter device 300.
[0059] The jet mill device 100 receives the material to be ground from a raw material tank (not shown) through a raw material input pipe 34. The material to be ground in the present disclosure is a mixed alloy powder, and has, for example, an average particle size of 10 μm or more and 500 μm or less. The average particle size (d50) in the present disclosure can be measured by an airflow dispersion type laser diffraction method (compliant with JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size means the particle size (median diameter) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%.
[0060] In the embodiment of the present disclosure, the average particle size (d50) is measured using a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec. Dispersion pressure: 4bar Measurement range: R2 Calculation mode: HRLD This indicates the d50 measured under the conditions above.
[0061] The raw material input pipe 34 is provided with multiple valves, and the internal pressure of the jet mill device 100 is appropriately maintained by opening and closing the valves. The material to be pulverized introduced into the jet mill device 100 is finely pulverized by collisions between the materials to be pulverized due to high-speed jets of inert gas from the nozzle pipe 36 and collisions with a collision plate installed to efficiently advance the pulverization. A humidification pipe is connected to the nozzle pipe 36 to add moisture to the inert gas.
[0062] Powder of alloys for RTB sintered magnets is active and easily oxidized. For this reason, as the gas used in the jet mill device 100, in order to avoid the risk of heat generation and fire and to reduce the oxygen content as an impurity to improve the performance of the magnet, dry (high purity) inert gases such as nitrogen, argon, and helium with a dew point of -60°C or less are generally used. However, in the embodiment of the present disclosure, the grinding is performed in a humidified state in which moisture is intentionally introduced into such inert gas. Details of this point will be described later.
[0063] The powder particles (fine powder) finely pulverized inside the jet mill device 100 are carried by the ascending air current and guided from the upper outlet to the inlet pipe 20 of the cyclone collector 200. Coarse particles that are not sufficiently pulverized are separated by a classifying rotor installed to classify coarse particles with a median diameter (d50) or more, remain inside the jet mill device 100, and are subjected to a further crushing process by collision. The classification of these coarse particles may be performed using a classifying rotor or centrifugal separation using a swirling flow. In this way, the material to be pulverized (mixed powder) fed into the jet mill device 100 is pulverized into fine powder with a particle size distribution of an average particle size (median diameter: d50) of 2.0 μm to 4.5 μm, and then moved to the cyclone collector 200.
[0064] The cyclone collector 200 is used to separate the powder from the airflow carrying the powder. Specifically, the mixed alloy powder (coarsely crushed powder) is crushed in a jet mill at the front stage, and the fine powder generated by the crushing is supplied to the cyclone collector 200 through the inlet pipe 20 together with the gas used for crushing. A mixture of an inert gas (crushing gas) and the crushed fine powder forms a high-speed airflow and is sent to the cyclone collector 200. The cyclone collector 200 is used to separate the crushing gas and the fine powder. The fine powder separated from the crushing gas is collected by the powder collector 50 through the exhaust port 40. The crushing gas is supplied to the bag filter device 300 through the outlet pipe 30. The bag filter device 300 collects very small particles, and clean gas is discharged to the outside through the exhaust port 32. For such solid-gas separation, it is possible to use a bag filter instead of the cyclone collector 200, but this would have a large impact on the environment and safety, such as the dispersion of fine powder into the air due to damage to the filter. Fine particles may be further separated from the gas separated by the cyclone collector by using a bag filter in combination.
[0065] One of the characteristic features of the present disclosure is that humidified pulverization is performed so that the oxygen content of the RTB sintered magnet is in the range of 1000 ppm or more and 3000 ppm or less. This makes it possible to suppress both nitridation of the powder particles due to pulverization and oxidation due to humidification, thereby obtaining high magnetic properties. As described above, normally, the increase in the oxygen content of the RTB sintered magnet due to the process after pulverization (mainly the process of producing a sintered body from the fine powder) is small (for example, 50 ppm or more and 300 ppm or less). Therefore, it is possible to adjust the amount of oxygen contained in the RTB sintered magnet by the pulverization process.
[0066] Specifically, the humidified inert gas in step (2) can be obtained by adding moisture to the inert gas in an amount of, for example, 0.5 g to 6.0 g per kg of the mixed alloy powder (coarsely pulverized powder).
[0067] The dew point in the grinding chamber and the amount of mixed alloy powder supplied to the jet mill depend on the grinding time and the size of the jet mill, but in a preferred embodiment, the inert gas is humidified so that the dew point during grinding is −65° C. to −30° C. In a further preferred embodiment, the rate at which the mixed alloy powder is supplied to the jet mill is 35 kg / hr to 180 kg / hr.
[0068] Examples of inert gases are nitrogen, argon, helium, and mixtures thereof. Among them, nitrogen is the most preferable because it is available at a low cost as a high-purity gas. Therefore, in a preferred embodiment, the inert gas is nitrogen gas. However, as a result of the study by the present inventors, when jet mill pulverization is performed using an inert gas made of nitrogen, it was found that when the average particle size of the resulting fine powder becomes 4.5 μm or less, the magnetic properties begin to deteriorate due to nitridation. In particular, it was found that when the average particle size becomes 3.5 μm or less, the deterioration of the magnetic properties due to nitridation may become significant. However, according to the embodiment of the present disclosure, since pulverization is performed in an appropriately adjusted humidified atmosphere, even if nitrogen gas is used as the inert gas, it is possible to suppress both nitridation and oxidation. This is thought to be because, even if the inert gas in the pulverization chamber is mainly nitrogen, by humidifying it so that it contains a specific adjusted amount of moisture, the active surface of the particles that appear by pulverization can be thinly oxidized before it is nitrided. The increase in oxygen content of the RTB sintered magnet due to the process after pulverization (mainly the process of producing a sintered body from the fine powder) is preferably 50 ppm to 300 ppm, more preferably 50 ppm to 200 ppm. To achieve this, as described below, wet pressing in a magnetic field or pressing in a magnetic field in an inert gas atmosphere is performed, and the resulting molded body is sintered. The average particle size of the fine powder in the process of obtaining the fine powder is more preferably 2.0 μm to 3.5 μm. By reducing the average particle size, it is possible to improve the magnetic properties.
[0069] (5) A process for producing a sintered body of fine powder In a preferred embodiment, the step of producing a sintered body of fine powder includes a step of producing a powder compact from the fine powder by pressing in a magnetic field, and a step of sintering the powder compact. In the case of pressing in a magnetic field, it is preferable to form the powder compact by pressing in an inert gas atmosphere or wet pressing from the viewpoint of suppressing oxidation. In particular, in the case of wet pressing, the surface of the particles constituting the powder compact is covered with a dispersant such as an oil agent, and contact with oxygen or water vapor in the air is suppressed. Therefore, it is possible to prevent or suppress oxidation of the particles by the air before, during, or after the pressing step.
[0070] When wet pressing in a magnetic field is performed, a slurry is prepared by mixing fine powder with a dispersion medium, and the slurry is supplied to a cavity in a mold of a wet pressing device and press-molded in a magnetic field.
[0071] ·Dispersion medium The dispersion medium is a liquid in which the alloy powder can be dispersed to obtain a slurry.
[0072] A preferred dispersion medium used in the present disclosure may be mineral oil or synthetic oil. Although the type of mineral oil or synthetic oil is not specified, if the kinetic viscosity at room temperature exceeds 10 cSt, the increased viscosity may strengthen the bonding force between the alloy powders, which may adversely affect the orientation of the alloy powder during wet compaction in a magnetic field. For this reason, the kinetic viscosity of the mineral oil or synthetic oil at room temperature is preferably 10 cSt or less. If the fractional point of the mineral oil or synthetic oil exceeds 400°C, it may be difficult to remove the oil after obtaining a compact, and the amount of residual carbon in the sintered body may increase, resulting in a deterioration of the magnetic properties. Therefore, the fractional point of the mineral oil or synthetic oil is preferably 400°C or less. Vegetable oil may also be used as the dispersion medium. Vegetable oil refers to oil extracted from plants, and the type of plant is not limited to a specific plant.
[0073] - Preparation of slurry The obtained alloy powder is mixed with a dispersion medium to obtain a slurry.
[0074] The mixing ratio of the alloy powder and the dispersion medium is not particularly limited, but the concentration of the alloy powder in the slurry is preferably 70% or more by mass ratio. 3 This is because, at a flow rate of 1000 / sec, the alloy powder can be efficiently supplied into the cavity and excellent magnetic properties can be obtained. The concentration of the alloy powder in the slurry is preferably 90% or less by mass ratio. The method of mixing the alloy powder and the dispersion medium is not particularly limited. The alloy powder and the dispersion medium may be prepared separately, and the mixture may be produced by weighing and mixing a predetermined amount of the alloy powder and the dispersion medium. When the mixed alloy powder is dry-pulverized with a jet mill or the like to obtain a fine powder, a container containing the dispersion medium may be placed at the alloy powder outlet of a pulverizing device such as a jet mill, and the fine powder obtained by pulverization may be directly collected in the dispersion medium in the container to obtain a slurry. In this case, it is preferable that the atmosphere inside the container is also made of nitrogen gas and / or argon gas, and the obtained alloy powder is directly collected in the dispersion medium without being exposed to the air to obtain a slurry. The slurry obtained in this way can be molded with a known wet press device to obtain a molded body having a predetermined size and shape. The molded body is sintered to obtain a sintered body.
[0075] Sintering process Next, the compact is sintered to obtain a rare earth sintered magnet body (sintered body). The compact is preferably sintered at a pressure of 0.13 Pa (10 -3 Torr) or less, preferably 0.07 Pa (5.0 x 10 -4 The sintering is carried out at a pressure of 1000 to 1150 Torr or less and at a temperature of 1000 to 1150°C. To prevent oxidation due to sintering, residual gas in the atmosphere may be replaced with an inert gas such as helium or argon. The obtained sintered body is preferably subjected to a heat treatment. The magnetic properties can be improved by the heat treatment. Known conditions can be used for the heat treatment, such as the heat treatment temperature and heat treatment time. The rare earth sintered magnet body thus obtained is subjected to a grinding / polishing process, a surface treatment process, and a magnetization process as necessary to complete the final rare earth sintered magnet.
[0076] The present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited thereto.
[0077] Experimental Example 1 The composition of RTB sintered magnets is roughly the same as that of samples No. 1 and 2 in Table 1. (mass%) The alloy was produced by strip casting so as to satisfy the following conditions (excluding O, C, and N). In Table 1 and Table 6 described later, the units for the O, C, and N compositions are not % by mass but ppm (mass ratio). The obtained alloys were coarsely pulverized by hydrogen pulverization to obtain coarsely pulverized powders. The average particle size of the coarsely pulverized powders was measured. The average particle size was in the range of 200 μm to 400 μm. In this disclosure, the average particle size refers to the particle size (median diameter) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%. The average particle size (d50) was measured using a particle size distribution measuring device "HELOS&RODOS" manufactured by Sympatec. Dispersion pressure: 4bar Measurement range: R2 Calculation mode: Measured under HRLD conditions.
[0078] Next, the additive alloy and the main alloy were prepared by strip casting so as to have the composition of No. a in Table 2 and No. A to C in Table 3. The obtained alloys were coarsely crushed by hydrogen crushing to obtain the additive alloy powder and the main alloy powder. The average particle size of the obtained alloy powders was in the range of 200 μm to 400 μm. The components of the obtained alloy powder were determined. Each component was measured by ICP emission spectrometry. The measurement results are shown in Tables 2 and 3. Next, the additive alloy powder and the main alloy powder were mixed in a V-type mixer under the mixing conditions in Table 4. No. 3 in Table 4 is a mixture of the additive alloy powder No. a and the main alloy powder No. A, and is a mixed alloy powder containing 5 mass% of the additive alloy powder (95 mass% of the main alloy powder). Nos. 4 to 7 are similarly described.
[0079] The coarsely pulverized powders of samples No. 1 and No. 2 and the mixed alloy powders of No. 3 to No. 7 were respectively put into the jet mill device 100 of FIG. 1 and pulverized to obtain fine powders. The pulverization conditions are shown in Table 5. No. 2 in Table 5 was humidified and pulverized by adding 1.4 g of moisture per 1 kg of the coarsely pulverized powder to an inert gas, and the amount of the coarsely pulverized powder supplied to the jet mill device was 64.1 kg / h. No. 1 and No. 3 to No. 7 are similarly described (No. 1 and No. 3 were pulverized without humidification). In this embodiment, nitrogen gas was used as the inert gas. The average particle size of the obtained fine powder is shown in Table 5. The fine powder was immersed in a mineral oil having a fractional point of 250° C. and a kinetic viscosity of 2 cSt at room temperature in a nitrogen atmosphere to prepare a slurry. The slurry concentration was 85% by mass. The obtained slurry was molded (wet molding) in a magnetic field to obtain a molded body. The molding device used was a so-called rectangular magnetic field molding device (horizontal magnetic field molding device), in which the magnetic field application direction and the pressure direction are perpendicular to each other. The obtained green body was sintered in a vacuum at 1040°C (a temperature selected so that sufficient densification by sintering occurs) for 4 hours to obtain a sintered body. The density of the sintered body was 7.5 Mg / m 3 The results were as above. The sintered body was then subjected to a heat treatment in which it was held at 800°C for 2 hours, cooled to room temperature, and then held at 500°C for 2 hours and cooled to room temperature to obtain a sintered body (RTB sintered magnet). The components of the obtained sintered magnet were determined. The contents of Nd, Pr, Tb, B, Co, Al, Cu, Ga, and Zr were measured by ICP emission spectrometry. Furthermore, O (oxygen content) was measured by gas fusion-infrared absorption method, N (nitrogen content) was measured by gas fusion-thermal conduction method, and C (carbon content) was measured by combustion-infrared absorption method using a gas analyzer. The results are shown in Tables 1 and 6. It was confirmed that all RTB sintered magnets No. 1 to 7 satisfied the [T] / 55.85>14×[B] / 10.8 of the present disclosure. The sintered magnets were machined to prepare samples with a length of 7 mm, width of 7 mm, and thickness of 7 mm, and the B content of each sample was measured using a BH tracer. r and H cJ The measurement results are shown in Table 7. [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6] [Table 7]
[0080] As shown in Table 1 (RTB-based sintered magnets made from single alloy powder) and Table 6 (RTB-based sintered magnets made from mixed alloy powders obtained by mixing additive alloy powders and main alloy powders), Nos. 1 to 7 have almost the same composition except for C, O, and N, and the average particle size (3.4 μm) of the fine powder obtained by jet mill pulverization is also the same. As shown in Table 3, all of the examples of the present invention (Nos. 4 to 6) have higher magnetic properties than Nos. 1 and 3, which were not humidified and pulverized. It has been thought that if the composition and particle size are almost the same, the magnetic properties will decrease as the amount of oxygen increases. However, as shown in Nos. 3 and 4 to 6, if the oxygen content is within the range of the RTB-based sintered magnets of the present disclosure, the magnetic properties are improved. Furthermore, even if humidified and pulverized, if the oxygen content is outside the range of the RTB-based sintered magnets of the present disclosure, the magnetic properties decrease as shown in No. 7. In addition, when comparing No. 1 and 2 (magnets made from single alloy powder with and without humidification) with No. 3 and 4 (magnets made from the mixed alloy powder of the present disclosure with and without humidification), No. 3 to 4 have higher B r and H cJ This shows that the magnetic properties can be further improved by subjecting the mixed alloy powder obtained by mixing the additive alloy powder and the main alloy powder of the present disclosure to humidification and milling. [Industrial Applicability]
[0081] The method for producing an RTB based sintered magnet according to the present disclosure can be used to produce permanent magnets for a wide variety of applications, such as voice coil motors (VCMs) for hard disk drives, motors for electric vehicles (EVs, HVs, PHVs), motors for industrial equipment, and other motors, as well as home appliances. [Explanation of symbols]
[0082] 100···Jet mill equipment, 200···Cyclone collection equipment, 300···Bag filter equipment
Claims
1. A method for producing an R-T-B based sintered magnet (R is at least one rare earth element and necessarily contains Nd; T is Fe or Fe and Co; when Co is contained, 90 to 100 mass % of the total amount of T is Fe and 0 to 10 mass % is Co), comprising the steps of: R1: (R1 is at least one rare earth element, and 50 mass% or more of the total of R1 is Pr) 33 to 69 mass%, B: 0.2 to 0.8% by mass, Cu: 0.8 to 3.0% by mass, Ga: 1.8 to 10% by mass, T: 15 to 60% by mass, Inevitable impurities, and At least one of Ag, Zn, In, Sn, Ti, Ge, Y, H, F, P, S, V, Ni, Mo, Hf, Ta, W, Nb, and Zr: 0 to 0.1 mass % or less; preparing an additive alloy powder comprising: R: 28.5 to 33.0% by mass, B: 0.80 to 1.0% by mass, Ga: 0.1 to 0.4% by mass, T: 64 to 70% by mass, Inevitable impurities, and At least one of Ag, Zn, In, Sn, Ti, Ge, Y, H, F, P, S, V, Ni, Mo, Hf, Ta, W, Nb, and Zr: 0 to 0.2 mass% or less; preparing a primary alloy powder consisting of: preparing a mixed alloy powder containing 1 to 16 mass % of the additive alloy powder and 84 to 99 mass % of the main alloy powder; supplying the mixed alloy powder to a jet mill having a milling chamber filled with an inert gas to mill the mixed alloy powder, thereby obtaining a fine powder having an average particle size of 2.0 μm or more and 4.5 μm or less; and preparing a sintered body of the fine powder. The Pr content of the additive alloy powder is greater than the Pr content of the main alloy powder, The inert gas is humidified, the R-T-B based sintered magnet has an oxygen content of 1000 ppm or more and 3000 ppm or less by mass ratio, R: 28.5% by mass or more and 33.0% by mass or less, B: 0.85% by mass or more and 0.91% by mass or less, Cu: 0.05% by mass or more and 0.50% by mass or less, Ga: 0.3% by mass or more and 0.7% by mass or less, T: 63% by mass or more and 70% by mass or less (T is Fe or Fe and Co) Inevitable impurities, and At least one of Ag, Zn, In, Sn, Ti, Ge, Y, H, F, P, S, V, Ni, Mo, Hf, Ta, W, Nb, and Zr: 0 to 0.2 mass% or less; It consists of: A method for producing an R-T-B based sintered magnet, which satisfies [T] / 55.85>14×[B] / 10.8, where [T] is the content (mass%) of T and [B] is the content (mass%) of B.
2. The method for producing a sintered R-T-B based magnet according to claim 1, wherein the R content of the sintered R-T-B based magnet is 31 mass % or less.
3. 3. The method for producing a sintered RTB based magnet according to claim 1, wherein the inert gas is nitrogen gas.
4. The step of preparing a sintered body of the fine powder includes: preparing a powder compact from the fine powder by wet pressing in a magnetic field or by pressing in a magnetic field in an inert gas atmosphere; sintering the powder compact; A method for producing a sintered R-T-B based magnet according to any one of claims 1 to 3, comprising:
5. 5. The method for producing a sintered R-T-B system magnet according to claim 1, wherein the fine powder in the step of obtaining the fine powder has an average particle size of 2.0 μm or more and 3.5 μm or less.
Citation Information
Patent Citations
Pulverizing treating device
JP1981045769A
Manufacture of permanent magnet
JP1992287304A
Manufacture of raw material powder for rare-earth magnet
JP1994140220A
Production of rare earth magnet
JP1996148317A
Double-alloy NdFeB rare earth permanent magnetic material and manufacturing method thereof
US20140328713A1
